An Ethnographic Case Study of Affordances in an Architecture Design Studio - Rands, Melissa L; Gansemer-Topf, Ann M (Teachers College record (1970), 2020)
Background/Context: Studio-based courses--the primary approach in design education--have been viewed as effective environments for learning. This study uses an ecological approach to explore how the studio environment creates opportunities for social interaction through immersive studies of studio learning. Purpose/Objective/Research Question/Focus of Study: We engaged in an ethnographic case study of a beginning architecture design course aimed at exploring the ways the learning environment of the studio affords social interaction, and how these interactions shape students' understandings and behaviors as they learn. Particular attention was paid to the physical, structural, and instructional affordances that contribute to learning in the studio environment. Setting: Over the course of one semester, we observed nine students and their instructor in Architecture Design 1 (AD 1), a first-year architecture studio at a large, public research institution. Population/Participants/Subjects: The student participants ranged in age from 18 to 25, four of the participants identified as students of color, two identified as international students, three identified as female, and six, male. The instructor, who identifies as female, had taught AD 1 at the university for eight years prior to the study and holds a master's degree in architecture. Research Design: We engaged in an ethnographic case study using an ecological approach, focused on the relationship between humans and their environment. We view learning and knowledge as individually constructed by the learner in a socially situated, public context; as such, a case study design using ethnographic methods of data collection was employed. Data Collection and Analysis: Our data sources included observations of daily studio activities, participant interviews, researcher reflections on studio visits, and course artifacts such as the course syllabus and assignment handouts. We analyzed data using a two-cycle method of coding and analysis focusing on identifying patterns or themes in the data. Findings/Results: We found several physical, structural, and instructional affordances that contribute to learning. The physical affordances of the studio environment of AD 1 included the open layout, public/private workspaces, and co-working in proximity to others. The structural affordances were long blocks of unscheduled work time, the project brief, and the sequencing of the projects, tasks, and deadlines. The instructional affordances included formal and informal critique, "mini-lectures," and demonstrations. Conclusions/Recommendations: Although focused within a design discipline, our findings have broader applicability to collegiate academic environments that support student learning. Recommendations include creating fluidity in the classroom space, centralizing feedback, demonstrating emerging understandings visually, and constraining constructivist learning environments.